Penjadwalan Proyek Dengan Metode Program Evaluation and Review Technique (PERT) - Nur Annisa Roziya; Ika Purnamasari; Wasono Wasono (Program Studi Statistika FMIPA Universitas Mulawarman, 2018)
Project scheduling is one of the techniques developed in operations research to solve management problems to obtain optimal solutions. One of the methods used for project scheduling is the method of Program Evaluation and Review Technique (PERT). In PERT method, three time estimates are used, that is optimistic time (a), pessimistic (b), and realistic (m). In this study, PERT method is used to determine the optimal duration and probability value of the completion of the Grand Sangatta housing project on house type 36 which is sourced from CV Miftah Collection. The data obtained are primary data and interview. Based on the results of the analysis, it can be know the activities that are on the critical path are the activities of making the foundation (B), concrete (D), wall (E), roof (H), ceiling (I), and painting (L). The minimum time duration of completion of type 36 homes is 34 days with a 50% confidence level which was originally scheduled for 60 days.